2×1 microstrip patch array antenna with harmonic suppression capability - Amir, N. A. (Institute of Electrical and Electronics Engineers Inc., 2016)
A 2×1 microstrip patch array antenna integrated with photonic bandgap (PBG) and stubs is designed and analyzed. The performance of the PBG and stubs structure are explained and analyzed in terms of the elimination of the resonance at the harmonic frequencies of the antenna. The proposed antenna is designed on FR-4 board with thickness of 1.6 mm and operated at 2.45 GHz frequency suitable for rectenna design application. From the simulated result, the first harmonic frequency (5.4 GHz), the second harmonic frequency (6.6 GHz) and the third harmonic frequency (7.8 GHz) are successfully suppressed. For instance, the radiation to the forward of the stubs-PBG antenna is suppressed at more than 15 dB at the second and third harmonic frequencies.